Comparison of clinical, laboratory and radiological characteristics between Chlamydia psittaci and adenovirus pneumonias: a multicenter retrospective study. (January 2023) - Li, Yi; Lin, Fengyu; Li, Wen; Chen, Gang; Li, Sha; Liu, Ben; Li, Haitao; Song, Chao; Lu, Rongli; Pan, Pinhua
Highlights: This study successfully distinguishes between Chlamydia psittaci and adenovirus pneumonia. C. psittaci pneumonia with more nervous system symptoms, higher C-reactive protein, and older age. Adenovirus pneumonia with more male, higher lymphocyte, and bilateral lung lesions. A developed nomogram may help avoid misdiagnosis and facilitate clinical decisions. Abstract: Objectives: Pneumonia caused by Chlamydia psittaci is a significant global public health issue. Symptom onset and laboratory characteristics may be confused with those of other respiratory viral infections, including adenovirus pneumonia. We aimed to determine differences in clinical presentations and establish a simple nomogram to differentiate C. psittaci and adenovirus pneumonias. Methods: We conducted a multicenter retrospective study in 10 tertiary general hospitals to compare patients with either C. psittaci (n = 78) or adenovirus (n = 102) pneumonia. A multivariable logistic regression model was used to identify risk factors of C. psittaci pneumonia that were used to establish a nomogram. Results: C. psittaci and adenovirus pneumonia showed certain similar clinical symptoms, including fever, dyspnea, and fatigue, but differed in other characteristics. The multivariate logistic regression showed that age, sex, nervous system symptoms, lymphocyte count, C-reactive protein level, and bilateral lung lesions were risk factors for C. psittaci pneumonia. After incorporating these six factors, the established nomogram achieved a good concordance value (0.949 [95% CI 0.917-0.982]) in differentiating the types of pneumonia, with well-fitting calibration curves. Conclusion: Despite having similar clinical features, the variables of age, sex, nervous system symptoms, lymphocytes, C-reactive protein levels, and bilateral lung lesions were combined into a clinically useful nomogram for the rapid and early differentiation of C. psittaci pneumonia from adenovirus pneumonia. This nomogram may help improve treatments and clinical outcomes.